2007
DOI: 10.1007/s10295-007-0249-x
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic study on the plasmid stability of three Lactococcus lactis strains

Abstract: The plasmid stability of three wild type Lactococcus lactis strains and their mutants was investigated at different incubation time and temperatures in two different media [M17 broth and reconstituted skim milk (RSM)]. The results showed that both incubation times and temperature are effective on plasmid loss. The plasmid profiles of wild type strains exhibited 8 to 9 distinct plasmid species with molecular weights from 2.1 to 24.0 kb. Lactose fermentation ability was found to be encoded by 22.2 (strain U70), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Based on the growth profile, the cells took about ~60 h to reach 100 generations. Recently, both incubation time and temperature were reported to have substantial effects on plasmid loss [49]. The researchers found that the incubation time had the most extreme effect on the stability of low molecular weight plasmids in Lactococcus cells where plasmid loss was observed after 72 h of cultivation while temperatures in the range of 15-40°C also stimulated plasmid instability.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the growth profile, the cells took about ~60 h to reach 100 generations. Recently, both incubation time and temperature were reported to have substantial effects on plasmid loss [49]. The researchers found that the incubation time had the most extreme effect on the stability of low molecular weight plasmids in Lactococcus cells where plasmid loss was observed after 72 h of cultivation while temperatures in the range of 15-40°C also stimulated plasmid instability.…”
Section: Discussionmentioning
confidence: 99%
“…All assays were performed in triplicates and the results are the means of three independent experiments. The plasmid genetics stability of the recombinant pHT43-SjLys/WB600 for continuous passage culture with chloramphenicol was determined through the method of Avsaroglu et al [2] and Leen et al [10]. For the strain, stability experiments were performed in triplicate too.…”
Section: The Growth Curve and Genetic Stability Of The Pht43-sjlys/ Wmentioning
confidence: 99%